ADH1B polymorphism, alcohol consumption, and binge drinking in Slavic Caucasians: results from the Czech HAPIEE study - Hubacek, Jaroslav A; Pikhart, Hynek; Peasey, Anne; Kubinova, Ruzena; Bobak, Martin (Alcoholism, clinical and experimental research, 2012)
BACKGROUND: Several genetic polymorphisms influence the risk of heavy alcohol consumption but it is not well understood whether the genetic effects are similar in different populations and drinking cultures, nor whether the genetic influences on binge drinking are similar to those seen for alcoholism. METHODS: We have analyzed the effect of the Arg47His (rs1229984) variant within the alcohol dehydrogenase (ADH1B) gene on a range of drinking related variables in a large Eastern European Slavic population (Czech HAPIEE study), which recruited random samples of men and women aged 45-69 years in 7 Czech towns (3,016 males and 3,481 females with complete data). Drinking frequency, annual alcohol intake, prevalence of binge drinking (≥100 g in men and ≥60 g in women at least once a month) and the mean dose of alcohol per occasion were measured by the graduated frequency questionnaire. Alcohol intake in a typical week was used to define heavy drinking (≥350 g/wk in men and ≥210 g in women). Problem drinking (≥2 positive answers on CAGE) and negative consequences of drinking on different aspects of life were also measured. RESULTS: The frequency of the His47 allele carriers was 11%. Homozygotes in the common allele (Arg47Arg), among both males and females, had significantly higher drinking frequency, and annual and weekly intake of alcohol than His47 carriers. The odds ratio of heavy drinking in Arg47Arg homozygotes versus His47 carriers was 2.1 (95% confidence intervals 1.1-3.2) in men and 2.2 (1.0-4.7) in women. In females, but not in males, Arg47Arg homozygotes had marginally significantly higher prevalence of binge drinking and mean alcohol dose per drinking session. There was no consistent association with problem drinking and negative consequences of drinking. CONCLUSIONS: The ADH1B genotype was associated with the frequency and volume of drinking but its associations with binge drinking and problem drinking were less consistent.
Keywords: White People; Alcohol Dehydrogenase; Alcohol Drinking; Humans; Czech Republic; missense mutace; lidé; Polymorphism, Genetic; Alcohol-Related Disorders; poruchy způsobené alkoholem; Female; pití alkoholu; lidé středního věku; Male; alkoholdehydrogenasa; polymorfismus genetický; senioři; Česká republika; Aged; běloši; Middle Aged; ženské pohlaví; mužské pohlaví; Mutation, Missense